Factors of the Active Listening of Preschool Children - Purić, Daliborka S. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Active listening is a communication skill which is crucial for the development of cooperative relationships in the group, culture of friendship and fellowship, it is also important for the development of literacy skills and talent for speaking. Furthermore, it contributes to the improvement of the level of knowledge, skills and school achievement, as well as to the development of self-confidence of children. Developing of active listening is an important task in the activities with children of preschool age. Preschool teacher is a key element of the training of preschool children in the area of the basic communication skills of active listening. In this sense, the results of our survey show that in the context of academic study programs for education of preschool teachers special attention is given to the communication skills and to their role in the development of active listening. But, bearing in mind the neglection of listening in comparison to other language skills, it is necessary to pay more attention to the improvement of the culture of listening, both in formal and nonformal, as well as in informal education and training of preschool teachers.